"Ship-from-store" strategy in platform retailing. (January 2021) - He, Yi; Xu, Qingyun; Shao, Zhen
Highlights: Effects of Ship-from-Store on the retailer's pricing decision and performance. How consumer heterogeneity affects the retailer's omnichannel operations. Identify the conditions under which the retailer benefits from ship-from-store. Impacts of charging expedited logistics service fee on both seller's profits. Abstract: In the omnichannel retailing context, some online-first retailers open the offline channel to implement cross-channel operational strategies to improve the consumer's experience. This paper develops an analytical model of the retailer's offline entry and omnichannel fulfillment option (i.e., the Ship-from-Store option) under competition through the platform's self-run store. In the omnichannel scenario, the retailer can provide time-sensitive consumers with a quick logistics service by implementing the Ship-from-Store option. We focus on the value of the Ship-from-Store option and explore the effects of this option on the pricing decisions of the retailer and platform. We also explore how consumer heterogeneities (time sensitivity and transportation costs) affect the retailer's omnichannel operations. In addition, we identify conditions under which the retailer can benefit from the Ship-from-Store option. Some managerial insights are provided.